Seasonal effects on ammonia, nitrous oxide, and methane emissions for beef cattle excreta and urea fertilizer applied to a tropical pasture - Cardoso, Abmael da Silva [UNESP]; Oliveira, Serena Capriogli [UNESP]; Janusckiewicz, Estella Rosseto; Brito, Liziane Figueiredo [UNESP]; Morgado, Eliane da Silva; Reis, Ricardo Andrade [UNESP]; Ruggieri, Ana Cláudia [UNESP] (Elsevier, 2019)
In this study we conducted four field trials (two wet- and two dry-season) to quantify N2O and CH4 emissions, NH3 volatilization, and N2O emission factors (EF3PRP) following the application of cattle dung, urine, dung plus urine, and urea fertilizer on a palisade-grass pastureland in Brazil. The EF3PRP differed with treatment and season. Wet season EF3PRP were 0.36%, 1.02%, and 0.84% and dry season EF3PRP were 0.32%, 0.47%, and 0.34% for dung, urine, and dung plus urine, respectively. These emission factors are maybe lower than the default proposed by the Intergovernmental Panel on Climate Change (IPCC; 2%). Methane emissions also differed according to the treatment and season, and annualized dung emissions were 0.54 kg CH4 head−1 year−1. The fraction of total-N from animal manure and urine emitted as NH3 (FracGASM) in the wet season for dung, urine and dung plus urine was 7.2%, 6.3%, and 6.4%, respectively; lower than the rate of dry season volatilization from urine (14.2%) and dung plus urine (11.5%). Observed FracGASM is probably lower than the IPCC guideline (20%). Emissions of N2O, CH4, and the volatilization of NH3 after urea treatment were not influenced by season; N2O emissions from urea were 0.85%, CH4 emissions were 112 g CH4-C ha−1, and N-fertilizer lost as NH3 was 16.9%. The emission factors observed in this experiment differed from the IPCC Guidelines; observed N2O emissions were lower than the guideline (1%), and FracGASF was higher than the 10% guideline.
Keywords: CH4 emission factor; Environmental impact of livestock; Greenhouse gases; N2O emission factor; Nitrogen cycle